Assessment of milkweed floss as a natural hollow oleophilic fibrous sorbent for oil spill cleanup. (15th August 2020) - Panahi, Shima; Moghaddam, Meghdad Kamali; Moezzi, Meysam
Abstract: Natural oil sorbent materials with a high oil sorption capacity have recently received remarkable attention for oil spill cleanup from seawater. This study reports on the development of a superhydrophobic hollow cellulosic fiber that could serve as an oil spill cleanup material. As oil sorption is based on the physical and chemical characteristics of the sorbent, FTIR, SEM, XRD, and surface contact angle of the fibers were determined. A series of tests were then carried out to analyze the sorption capacity, dynamic oil retention, and reusability. Subsequently, the effect of the fibers' weight on the amount of oil absorption and absorption time was investigated. The wettability analyses showed that the milkweed floss fiber possessed a superhydrophobic characteristic (with the water contact angle of 140°). The empty channel of the fiber was more than 90% of its total volume. The hydrophobicity and capillary properties helped the fibers to absorb up to 100 g/g of oil, which was higher than that obtained by many natural cellulosic fibers. Graphical abstract: Image 1 Highlights: The sorbent was prepared by milkweed floss fibers. It possesses a superhydrophobic characteristic with a water contact angle of 140°. The Milkweed fibers have an oil sorption capacity of more than 100 g/g of oil. The packaged weight of 0.2 g resulted in the faster oil sorption. More than 90% of sorption capacity absorb after 3 min.